(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Postpartum period is one of the sensitive time of woman’s life when she is in contact with health care facility and when both mother and newborn need a special care. For the purpose of preventing unwanted pregnancies and maximizing the time between pregnancies, effective contraception should be discussed and offered at that time. The risk of problems may rise if an intrauterine device (IUD) is implanted during the postpartum period at different times or by various methods. Aim and Objective: The present study was aimed to examine complication of IUCD insertion in postpartum period with Interval period. Methodology: This prospective observational study was conducted within a time period of two years from September 2015 to August 2017 at Department of Obstetrics and Gynaecology, Santosh Medical College and Hospital, Ghaziabad. Total 265 IUCD insertions were done. Out of this, 125 cases were of postpartum (post placental and intra caesarean) and 140 were interval insertions. Result: Majority of the cases who accepted PPIUCD belonged to the age group upto 25 years (56.7%) and those in Interval belonged to 26-30 years (41.6%). Majority of the patients in study belonged to lower middle class : PPIUCD (66.7%) and Interval (48.8%), according to the modified Kuppuswami classification. In both the groups, IUCD insertions was done more in multiparous women. . There were 11 expulsions in PPIUCD group (9.2%) and 3 in Interval group (2.4%) . Conclusion: The study concluded PPIUCD method should be popularized across the country as an option to all women undergoing institutional deliveries, in tertiary health centres irrespective of the mode of delivery.